Distribution of Calretinin Immunoreactivity in the Lateral Nucleus of the Bottlenose Dolphin (Tursiops truncatus) Amygdala. Issue 11 (17th July 2017) - Rambaldi, A.M.; Cozzi, B.; Grandis, A.; Canova, M.; Mazzoni, M.; Bombardi, C.
ABSTRACT: The amgdaloid complex consists of different nuclei, each with unique cytoarchitectonic, chemoarchitectonic and connectional characteristics. Most of the inputs coming from cortical and subcortical areas enter the amygdala via the lateral nucleus, which makes it the main receiving structure of the complex. The activity of its neurons is coordinated and modulated by different inhibitory, GABAergic‐interneurons, which can be classified for their expression of various calcium‐binding proteins, as well as by morphological characteristics. This research based on the analysis of the amygdala of three bottlenose dolphins, provides the first description of the topography, cytoarchitecture and distribution of calretinin immunoreactivity of the lateral nucleus. Our observations on the bottlenose dolphin confirmed the general topography of the mammalian amygdala and of the lateral nucleus. Notably, we identified six subdivision of the nucleus, more than those reported until now in the rat, monkey and human lateral nucleus. This could reveal an outstanding capability of integration and elaboration of external stimuli. In addition, we observed a strong presence of CR‐immunoreactive (‐ir) neurons and fibres. CR‐ir neurons were mainly non‐pyramidal inhibitory neurons; in particular, 80% of IR‐cells were represented by large and small polygonal neurons. In the lateral nucleus of the human amygdala, CR‐ir neurons form inhibitory synapses on calbindin‐D28k‐IR inhibitory interneurons. Since calbindin‐D28k‐ir interneurons make inhibitory synapses on the pyramidal cells, the final goal of the CR‐ir interneurons could be the synchronization of cells activity, thus playing an important role in the control of information flow in the lateral amygdalar nucleus. Anat Rec, 2017. © 2017 Wiley Periodicals, Inc. Anat Rec, 300:2008–2016, 2017. © 2017 Wiley Periodicals, Inc.